Suppression of Berberine and Probiotics (in vitro and in vivo) on the Growth of Colon Cancer With Modulation of Gut Microbiota and Butyrate Production - Huang, Chao; Sun, Ying; Liao, Sheng-rong; Chen, Zhao-xin; Lin, Han-feng; Shen, Wei-zeng (Frontiers in Microbiology, 2022)
Background and Objective An increasing number of evidence has revealed that the gut microbiome functions in immunity, inflammation, metabolism, and homeostasis and is considered to be crucial due to its balance between human health and diseases such as cancer, leading to the emergence of treatments that target intestinal microbiota. Probiotics are one of them. However, many challenges remain regarding the effects of probiotics in cancer treatment. Berberine (BBR), a natural extract of Rhizoma Coptidis and extensively used in the treatment of gastrointestinal diseases, has been found to have antitumor effects in vivo and in vitro by many recent studies, but its definite mechanisms are still unclear. This study aimed to explore the inhibitory effect of BBR and probiotics on the growth of colon cancer cells in vitro and in vivo, and the regulatory influence on the gut microbiome and butyrate production. Methods Colon cancer cell line HT29 was used to establish a xenograft model of nude mice and an in vitro model. A total of 44 nude mice and HT29 cells were divided into control, model, model + BBR, model + probiotics, and model + combination of BBR with probiotics (CBPs). Live combined Bifidobacterium, Lactobacillus, and Enterococcus powder (LCBLEP) was used as a probiotic preparation. LCBLEP was cultured in the liquid medium under anaerobic conditions (the number of viable bacteria should reach 1 × 108CFU), and the supernatant was collected, and it is called probiotic supernatant (PS). Model + BBR and model + probiotics groups were treated with BBR and LCBLEP or PS for 4 weeks in vivo or 48, 72, and 96 h in vitro, respectively. Tumor volume or cell proliferation was measured. Gut microbiota was pyrosequenced using a 16S rDNA amplicon. HDAC1 mRNA level in HT29 cells and sodium butyrate (SB) expression in the serum of mice was detected by QPCR and ELISA. Results The treatment of BBR and CBP reduced the growth of neoplasms in mice to a different extent (p > 0.05), especially at 14 days. The inhibitory effect of LCBLEP on tumor growth was more significant, especially at 11–21 days (p < 0.05). Inhibition of BBR on in vitro proliferation was concentration-dependent. The suppression of 75% probiotic supernatant (PS) on the proliferation was the most significant. The supplement of LCBLEP significantly increased the richness and evenness of the gut microbe. BBR dramatically increased the abundance of Bacteroidetes and Proteobacteria, with reduced Ruminococcus, followed by the LCBLEP. The LCBLEP reduced the relative abundance of Verrucomicrobia and Akkermansia, and the CBP also promoted the relative level of Bacteroidetes but reduced the level of Verrucomicrobia and Akkermansia. BBR and LCBLEP or CBP improved the alpha and beta diversity and significantly affected the biomarker and metabolic function of the gut microbe in nude mice with colon cancer. The level of HDAC1 mRNA was reduced in HT29 cells treated with BBR or PS (p < 0.05), the mice treated with BBR revealed a significantly increased concentration of SB in serum (p < 0.05), and the inhibitory effect of SB on the proliferation of HT29 cells was stronger than panobinostat and TSA. Conclusion Although the combination of BBR and probiotics has no advantage in inhibiting tumor growth compared with the drug alone, BBR can be used as a regulator of the intestinal microbiome similar to the probiotics by mediating the production of SB during reducing the growth of colon cancer.